Evidence of a Disk Wind Origin for Fluorescent H2 in Classical T Tauri Stars - Matt Kalscheur; Kevin France; Brunella Nisini; P. Christian Schneider; Richard Alexander; Jochen Eislöffel; Justyn Campbell-White; Hsien Shang; Manuele Gangi; Zhen Guo; Seok-Jun Chang (The Astronomical Journal)
We use far-ultraviolet spectra of 36 T Tauri stars, predominately from the Hubble Space Telescope (HST) ULLYSES program, to examine the kinematic properties of fluorescent H _2 emission lines for evidence of disk outflows. Leveraging improvements to the HST Cosmic Origins Spectrograph wavelength solution, we coadd isolated lines within four fluorescent progressions ([ v’ , J’ ] = [1,4], [1,7], [0,2], and [3,16]) to improve signal-to-noise ratio (S/N), and we fit each coadded line profile with one or two Gaussian components. Of the high-S/N line profiles (S/N ≥ 12 at the peak of the profile), over half are best fit with a combination of a broad and a narrow Gaussian component. For profiles of the [1,4] and [1,7] progressions, we find a systematic blueshift of a few kilometers per second between the broad and narrow centroid velocities and stellar radial velocities. For the [0,2] progression, we find centroid velocities consistently blueshifted with respect to stellar radial velocities on the order of −5 km s ^−1 for the single and narrow components, and −10 km s ^−1 for the broad components. Overall, the blueshifts observed in our sample suggest that the molecular gas traces an outflow from a disk wind in some sources, and not solely disk gas in Keplerian rotation. The low-velocity systematic blueshifts, as well as emitting radii as inferred from line FWHMs, observed in our sample are similar to those observed with optical [O i ] surveys of T Tauri stars. We estimate H _2 mass-loss rates of 10 ^−9 to 10 ^−11 M _⊙ yr ^−1 , but incomplete knowledge of wind parameters limits comparisons to global models.